Reference standards for flow cytometric estimation of absolute nuclear DNA content in plants. Issue 9 (18th August 2021) - Temsch, Eva M.; Koutecký, Petr; Urfus, Tomáš; Šmarda, Petr; Doležel, Jaroslav
Abstract: The estimation of nuclear DNA content has been by far the most popular application of flow cytometry in plants. Because flow cytometry measures relative fluorescence intensities of nuclei stained by a DNA fluorochrome, ploidy determination, and estimation of the nuclear DNA content in absolute units both require comparison to a reference standard of known DNA content. This implies that the quality of the results obtained depends on the standard selection and use. Internal standardization, when the nuclei of an unknown sample and the reference standard are isolated, stained, and measured simultaneously, is mandatory for precise measurements. As DNA peaks representing G1 /G0 nuclei of the sample and standard appear on the same histogram of fluorescence intensity, the quotient of their position on the fluorescence intensity axis provides the quotient of DNA amounts. For the estimation of DNA amounts in absolute units, a number of well‐established standards are now available to cover the range of known plant genome sizes. Since there are different standards in use, the standard and the genome size assigned to it has always to be reported. When none of the established standards fits, the introduction of a new standard species is needed. For this purpose, the regression line approach or simultaneous analysis of the candidate standard with several established standards should be prioritized. Moreover, the newly selected standard organism has to fulfill a number of requirements: it should be easy to identify and maintain, taxonomically unambiguous, globally available, with known genome size stability, lacking problematic metabolites, suitable for isolation of sufficient amounts of nuclei, and enabling measurements with low coefficients of variation of DNA peaks, hence suitable for the preparation of high quality samples.